Analysis of Autism Students at SKH Al-Ihsan 02 Cilegon City - Sufiyati, Uuf; Nadirah, Yahdinil Firda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Researchers conducted observations at the school because they wanted to ensure that education, attention, support and communication were optimal to help autistic students adapt to their environment. Children with autism must also be educated to help them behave like other normal children. This education must be provided by parents and their families, not just by teachers at school. Children with autism also need extra support and attention from their parents and families. Parents who have children with autism must know how to care for and accompany them to support their development and build social interactions, such as helping them learn, play and interact with other people. Additionally, communication is a particularly difficult challenge for people with autism; Parents can try several approaches to build communication with children with autism, such as imitating their child's sounds and play behavior to encourage more interaction.